Improving inclusion and well-being of trans and gender nonconforming collegiate student–athletes: foundational concepts from the National Collegiate Athletic Association Summit on Gender Identity and Student–Athlete Participation. (20th March 2023) - Kroshus, Emily; Ackerman, Kathryn E; Brown, Mac; Griffin, Pat; Durden, LaGwyn; Merrill, Jean; Wilson, Amy; Hainline, Brian
Abstract : The National Collegiate Athletic Association (NCAA) Summit on Gender Identity and Student–Athlete Participation was convened to identify institutional/athletic department strategies that may support the well-being of trans and gender nonconforming (TGNC) collegiate student–athletes in the USA. The Summit's purview did not include policy-level changes to eligibility rules. A modified Delphi consensus process was used to identify strategies for supporting collegiate TGNC student–athlete well-being. Key steps included an exploration phase (learning, generating ideas), and an evaluation phase (rating ideas in terms of their utility and feasibility). Summit participants (n=60) included individuals meeting at least one of the following criteria: current or former TGNC athlete, academic or healthcare professional with topical expertise, collegiate athletics stakeholder who would be involved in implementing potential strategies, representative from leading sports medicine organisation, or representative from relevant NCAA membership committee. Summit participants identified strategies in the following domains: healthcare practices (patient-centred care and culturally sensitive care); education for all stakeholders involved in athletics; and administration (inclusive language, quality improvement processes). Summit participants also proposed ways that the NCAA, through its existing committee and governance structures, could help support the well-being of TGNC athletes. NCAA-focused concepts were in the following domains: policy making processes; eligibility and transfer processes; resource development and dissemination; and visibility and support for TGNC athletes. The strategies developed represent important and relevant approaches that member institutions, athletic departments, NCAA committees, governance bodies and other stakeholders might consider in their efforts to support TGNC student–athlete well-being.